I was wondering: reflections on collaborative practice by five researchers in Australia, New Zealand and the United States. Issue 5 (3rd September 2021) - Prout, Peter F.; Wolgemuth, Jennifer R.; Gray, Christina C.; Lowe, Geoffrey M.; Thorpe, Vicki; Killam, Rachel
ABSTRACT: The catalyst for this article stems from my reflections (Peter) on the efficacy of collaborative engagement I recently experienced with colleagues in my university and similar institutions in the United States (US) and New Zealand (NZ). Accordingly, I invited research scholars (Christina and Geoffrey) from Australia, (Vicki) from NZ and (Jenni and Rachel) from the US to reflect upon the connectedness, care and community they experienced from collaboration in research projects with me. The framework I chose for their sharing was the Harvard Visible Thinking Routine; 'I see, I think, I wonder' (2009). The purpose of this article is to highlight the potential outcomes of reflective practice as researchers in three countries share their perceptions and perspectives concerning their experiences of connectedness and community in confronting isolation and neo-liberal challenges that we encounter in our research endeavours. Each person shares their unique ontological experiences as researchers, including how these experiences transformed their views concerning the value they ascribe to collaboration in relation to their work. Finally, despite our diverse ontological perspectives and geographic separation, we highlight authentic sharing among scholars internationally as an invaluable practice to potentially alleviate the lived experiences of isolation and separation that research scholars may acknowledge in their work.